The Potential of Distance Learning within the Course “History of Linguistic Studies” - Sergiy Lukyanenko (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The transformation of the educational space at the beginning of the 21st century involves the further improvement of academic disciplines and students' competencies. The distance learning system (DLS) Moodle provides new opportunities for this.